Strategies to improve teaching of information, communication and technology by grade two teachers of Chikato cluster in Shurugwi district - Maera, Joyce (Midlands State University, 2020)
The purpose of the research was to find strategies to improve the teaching of Information, Communication and Technology by grade two teaches of Chikato Cluster in Shurugwi District. To carry out the study the researcher used descriptive method. A sample of five school were used by the researcher to carry out the study. The sample was made up of fifteen participants, ten teachers and five schools heads. The researcher used purposively sampling techniques in sampling the participants. Questionnaires, interviews and observation were used for data collection. The findings from the sample were presented in the form of tables and themes which were discussed and linked with related literature. Findings from the study revealed that the main strategies to improve teaching ICT by grade learners were provision of adequate computers, in-service training of teachers in ICT, use of solar energy where there is no electricity and introducing computer levy in schools.